Immunohistochemical study of CD34 in tooth eruption by using amniotic stem cells - Jassim, Lubna K; Al- Hijazi, Athraa Y (Journal of Baghdad College of Dentistry, 2013)
Background: Tooth eruption is a more general process, however, which includes certain posteruptive tooth movements. There are two fundamental requirements for both tooth eruption to occur: (1) Require soft tissue, intervening between tooth structure and alveolar bone, which plays an important role in regulating the remodeling of adjacent tissues. (2) Require bone turnover that is temporally and spatially regulated to facilitate specific translocations of teeth through alveolar bone These amniotic stem cells are multipotent and able to differentiate into various tissues, which may be useful for human application and recently it used in many medical branches. CD34 is an endothelial marker that is extensively used in immunohistochemistry and most vascular endothelial cells. Expression of the stem cell antigen CD34 is a defining hallmark of hemopoietic stem cells and progenitors. This study aimed to study the expression of CD34 by dental cells involved in tooth eruption after administration of amniotic stem cell Materials and Methods: forty eight albino Swiss mice of one day old age injected with isolated amniotic stem cells in the anterior region of maxilla (incisors area) other 16 mice injected with saline represents control. Sacrifice 4 mice for each period (4, 7, 10, and 13) day old age. The result were studied histologically and immunohistochemistry. Results: Immunohistochemical result revealed positive expression of CD34 in pulp (Vascular, Paravascular), Mesenchymal cell and in the Dental sac of different groups. Coincidence test of expression marker CD34 in various studied group shows that Chorion application affected on CD34 expression in pulp while Amniotic fluid affected on dental sac.Conclusion Immunohistochemical study of expression marker CD34 in various studied groups show that chorion application affected on CD34 in pulp .While amniotic fluid affected on dental follicle.